(untitled) (TAJ: Journal of Teachers Association, 2009)
The study was carried out to see the prevalence and pattern of extrapulmonary tuberculosis in Rajshahi. Twenty five hundred eighty two tuberculosis patients (sputum positive, sputum negative and extrapulmonary) who were diagnosed and treated in between January 1999 and December 2003 in Rajshahi Chest Disease Clinic and Chest Disease Hospital were included in this study. Extrapulmonary tuberculosis accounted for about 16% of total tuberculosis cases. Tuberculous lymphadenitis was found to be the commonest form of extrapulmonary tuberculosis, comprising about 75% of the extrapulmonary cases. Tuberculous pleural effusion was noted in about 9% of cases, intestinal tuberculosis in 7%, bone and joint tuberculosis in 5% and other forms in 4% cases. 24% patients with extrapulmonary tuberculosis were afebrile, 14% had normal ESR, and 22% had negative Mantoux test. doi: 10.3329/taj.v17i1.3484 TAJ 2004; 17(1) : 16-19